50 Bauhaus Icons : You should know - Straßer, Josef (Munich ; London ; New York : Prestel, 2018)
Feininger, Lyonel ; Itten, Johannes ; Kerkovius, Ida ; Keler, Peter ; Dell, Christian ; Schmidt, Joost ; Breuer, Marcel ; Buscher, Alma ; Slutzky, Naum ; Bayer, Herbert ; Bogler, Theodor ; Hartwig, Josef ; Moholy-Nagy, László ; Gropius, Walter ; Meyer, Adolf ; Pap, Gyula ; Lindig, Otto ; Muche, Georg ; Albers, Josef ; Schmidt, Kurt ; Kandinsky, Wassily ; Wagenfeld, Wilhelm ; Dieckmann, Erich ; Hirschfeld-Mack, Ludwig ; Tümpel, Wolfgang ; Rittweger, Otto ; Brandt, Marianne ; Moholy, Lucia ; Albers, Anni ; Przyrembel, Hans ; Stölzl, Gunta ; Bredendieck, Hin ; Peterhans, Walter ; Klee, Paul ; Gautel, Hermann ; Schlemmer, Oskar
boek